Analisis Peran Pelatih Tinju dalam Pengembangan Mental Atlet untuk Mengatasi Kecemasan Bertanding - Dhika Kurniawan; Tedi Supriyadi; Aam Ali Rahman (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the role of boxing coaches in the mental development of athletes to overcome competition anxiety. This study uses a descriptive qualitative approach. The research subjects consisted of coaches and boxing athletes involved in the training and competition process. The data collection technique was carried out through in-depth interviews and documentation. Data analysis was carried out using thematic analysis techniques with the help of NVivo software to carry out the process of coding data, identify research themes, and visualize the relationships between concepts. The results of the study show that coaches have an important role in the mental development of athletes through providing motivation, psychological support, effective communication, and mental coaching during the training process. NVivo's visualization shows that coaches' motivation and mental support are the dominant factors that help athletes control competition anxiety and increase confidence. The findings of this study show that coaches not only play a role in improving athletes' technical skills, but also in building athletes' mental readiness to face competitive pressure optimally. Keywords: boxing coach, athlete mentality, competition anxiety, NVivo